Effect of the Thickness of Stabilized Cemented Sand Soil in the Bearing Capacity of Shallow Foundation - Younes, Samar Abd ALhameed; Thajeel, Jawad Kadhim (الجمعية العلمية للدراسات التربوية المستدامة, 2023)
The main aim of this paper is to examine the effectiveness stabilized cemented soil on dense sand has been gathered from loading tests carried on model of square steel footing with (89,89,23) mm length, width and thickness, resting on cement-improved layers of various thicknesses, considering the affected of soil-cement layer thickness (H) on the bearing capacity of square footing. Four different values of the relation thickness of reinforced layer divided by footing width (H/B) were tested, corresponding to 0.1, 0.3, 0.6, and 1. The sand layers compacted with dry unit weight (15.8 kN/m3), thus, achieving the state of dense soils (Dr=77%). Result showed that the (H/B) ratio affected the stress-settlement curves and increased bearing capacity with increasing H/B ratio. The results also showed two mechanisms of failure, the cement- reinforcement soil layer broke, showing a fissure was located close the footing’s edge and central axis or it was located close the footing’s edge only, according to the thickness of the reinforced layer.
Keywords: التربة الأسمنتية -- ميكانيكا التربة -- الهندسة المدنية